Association Analysis of IL10, TNF-α, and IL23R-IL12RB2 SNPs with Behçet’s Disease Risk in Western Algeria - Khaib Dit Naib, Ouahiba (Frontiers Media S.A., 2013)
Objective: We have conducted the first study of the association of interleukin (IL)-10, tumor necrosis factor alpha (TNF-α), and IL23R-IL12RB2 region single nucleotide polymorphisms (SNPs) with Behçet’s disease (BD) in Western Algeria. Methods: A total of 51 BD patients and 96 unrelated controls from West region of Algeria were genotyped by direct sequencing for 11 SNPs including 2 SNPs from the IL10 promoter [c.-819T > C (rs1800871), c.-592A > C (rs1800872)], 6 SNPs from the TNF-α promoter [c.-1211T > C (rs1799964), c.-1043C > A (rs1800630), c.-1037C > T (rs1799724), c.-556G > A (rs1800750), c.-488G > A (rs1800629), and c.-418G > A (rs361525)], and 3 SNPs from the IL23R-IL12RB2 region [g.67747415A > C (rs12119179), g.67740092G > A (rs11209032), and g.67760140T > C (rs924080)]. Results: The minor alleles c.-819T and c.-592A were significantly associated with BD [odds ratio (OR) = 2.18; 95% confidence interval (CI) 1.28–3.73, p = 0.003]; whereas, there was weaker association between TNF-α promoter SNPs or IL23R-IL12RB2 region and disease risk. Conclusion: Unlike the TNF-α and the IL23R-IL12RB2 region SNPs, the two IL10 SNPs were strongly associated with BD. The -819T, and -592A alleles and the -819TT, -819CT, and -592AA and -592CA genotypes seem to be highly involved in the risk of developing of BD in the population of Western Algeria.